‎Predicting mental health based on psychological hardiness, emotional intelligence and cognitive triad in mothers with slow learning students - Rostami, maryam; Sameti , Nahid; Mahdinejad gorji , Galin; Abarghoo , Saeedeh (Applied Family Therapy Journal (AFTJ), 2020)
Aim: The aim of the present study was to predict mental health based on psychological hardiness, emotional intelligence and cognitive triad in mothers with slow-learning students. Method: The research method was descriptive and correlational. The statistical population consisted of 132 mothers with Slow-Learning student’s reffering to school for slow learners during 2017-2018 in Tehran. From this community 78 mothers were selected through non-probability and convenience sampling method and responded to Ahvaz hardiness inventory (1998), Petrides and Furnhams emotional intelligence scale (2001), Beckham’s cognitive triad inventory (1986) and Goldberg general health questionnaire (1979). The data were analyzed by multiple regression Inter method. Results: The results showed that psychological hardiness can predict the mental health of mothers with slow-learning students (P = 0.01, β= 0.41). The results also showed that the components of emotional intelligence (P = 0.01), components of optimism and control of emotions (P = 0.01) & among cognitive Triad components, view to self and view to future (P = 0.01) can predict mothers’ mental health. Conclusion: Cognitive personality and high emotional intelligence as well as positive perspective to self and future in mothers with slow-learning student can lead to their mental health.